RELATIONSHIP BETWEEN AGE, DURATION OF USE AND PREGNANCY POST-ACCEPTORS OF PROGESTIN CONTRACEPTION IN GUWOSARI VILLAGE, PAJANGAN, BANTUL, YOGYAKARTA - wiwin Hindriyawati; widy Nurwiandani; Sri Untari (JURNAL KESEHATAN INDRA HUSADA, 2021)
Background: Myths about contraception discourage some women from doing family planning programs. In fact, family planning is presented so that husbands and wives have the opportunity to do careful planning before finally having children, such as financial planning to education. Myth: Contraceptive use causes difficulty getting pregnant (CNN Indonesia, 2019). Methods: cross sectional study design. sample of pregnant with post-Progestin contraception, 32 respondents. Results: There is a relationship between age and pregnancy of post-acceptor progestin (p = 0.001), there is no relationship between duration of use and pregnancy (p = 0.237). Progestin injection for 3 months had an average pregnancy of 20.6 months, implant acceptors had an average time of 14.6 months, and reproductive age of 20-35 years the minimum pregnancy was 1 month waiting. Conclusion: pregnancy is related to age and not related to the length of contraceptive use. Keywords: Pregnancy, Duration of Use, Post acceptor Progestin, Age